Heavy Metal Pollution Reduced the Potentiality of Pen Culture in the Wetland Aquaculture in an Urban Area of Bangladesh - Nahida Islam; Dinesh Chandra Shaha; Jahid Hasan; Md. Hafij Al Asad; Mohammad Abdus Salam; Murshida Khan; Sampa Rani Kundu; Minhaz Ahmed (Conservation, 2022)
The Belai beel serves as an important aquatic resource for the livelihood of the local community of the Gazipur district in Bangladesh. However, water pollution in recent times, mainly from industrial wastes and sewage effluents, may disrupt its aquatic environment. Thus, the purpose of the present study was to assess the potential area of pen fish culture in the Belai beel. The study was performed in the Rajbagan (L1), Kamaria (L2) and Rewla (L3) areas of the Belai beel. Grass carp, silver carp, common carp, catla and rui of 20–30 cm in size were stocked at a rate of 15,000 fish/ha and reared for 150 days in pens installed in the L1, L2 and L3 areas, respectively. The fishes were fed with mustard oil cake and rice bran. Maximum fish production was found in Rewla (12.97 ton/ha/150 days) compared to Rajbagan (8.85 ton/ha/150 days) and Kamaria (10.67 ton/ha/150 days) due to it having comparatively good quality water. There were significant differences in metal ion concentrations (p < 0.05) among the three fish pens. In the Rajbagan area, concentrations of Cd and Cu in the water coming from the industrial effluent canal exceeded the acceptable limit. Results indicated that the Rewla area was better than Rajbagan and Kamaria due to it having relatively good quality water for pen fish culture.